Cardiac Power Output Is Independently and Incrementally Associated With Adverse Outcomes in Heart Failure With Preserved Ejection Fraction. (February 2022) - Harada, Tomonari; Yamaguchi, Miho; Omote, Kazunori; Iwano, Hiroyuki; Mizuguchi, Yoshifumi; Amanai, Shiro; Yoshida, Kuniko; Kato, Toshimitsu; Kurosawa, Koji; Nagai, Toshiyuki; Negishi, Kazuaki; Anzai, Toshihisa; et al.
Abstract : Background: Cardiac power output is a measure of cardiac performance, and its prognostic significance has been shown in heart failure (HF) with reduced ejection fraction. Patients with HF with preserved ejection fraction may have altered cardiac performance, but the prognostic relevance of cardiac power output is unknown. This study sought to determine the association between cardiac power output and clinical outcomes in HF with preserved ejection fraction and to compare its prognostic effect to other measures of cardiac performance including ventricular-arterial coupling and mechanical efficiency. Methods: Cardiac power output normalized to left ventricular mass was assessed by echocardiography in 408 patients with HF with preserved ejection fraction. Load-independent contractility (end-systolic elastance), arterial elastance, its coupling (arterial elastance/end-systolic elastance), left ventricular global longitudinal strain, and mechanical efficiency (stroke work/pressure-volume area) were also estimated noninvasively. The primary end point was a composite of cardiovascular mortality or HF hospitalization. Results: The primary composite outcome occurred in 84 patients during a median follow-up of 19.4 months. There was a dose-dependent association between cardiac power output and the composite outcomes, in which patients with the lowest tertile of cardiac power output had >3-fold risk than those with the highest tertile (hazard ratio, 3.04 [95% CI, 1.66–5.57]; P =0.0003). In a multivariable model, lower cardiac power output was independently associated with adverse outcomes (hazard ratio, 0.70 per 1 SD [95% CI, 0.49–0.97]; P =0.03). In contrast, left ventricular size, end-systolic elastance, arterial elastance, arterial elastance/end-systolic elastance ratio, and left ventricular mechanical efficiency were not associated with outcomes. Cardiac power output provided an incremental prognostic effect over the model based on clinical (age, gender, diastolic blood pressure, and atrial fibrillation) and echocardiographic markers (left atrial size, pulmonary pressures, global longitudinal strain, and the ratio of early diastolic mitral inflow velocity to early diastolic mitral annular tissue velocity; P =0.03). Conclusions: In patients with HF with preserved ejection fraction, cardiac power output was independently and incrementally associated with adverse outcomes whereas other markers of cardiac performance were not. Abstract : Supplemental Digital Content is available in the text.